Assessing the impacts of urbanization on stream ecosystem functioning through investigating litter decomposition and nutrient uptake in a forest and a hyper-eutrophic urban stream - Jie Gao; Yuyue Huang; Yue Zhi; Jingmei Yao; Fang Wang; Wei Yang; Le Han; Dunmei Lin; Qiang He; Bing Wei; Khara Grieger (Ecological Indicators, 2022)
Rapid urbanization significantly affects freshwater systems by interfering with important ecological functions. The responses of different ecosystem functions in urban streams and their potential ecological effects remain largely unknown, impeding their management and restoration in many cases. In this study, we simultaneously assessed two important ecosystem functions, litter decomposition and nutrient uptake, and investigated the associated microbial and benthic macroinvertebrate communities in two subtropical streams (i.e., a forest headwater stream as a reference and an urban stream that was hyper-eutrophic). Litter decomposition was estimated using litter bags with two mesh sizes (i.e., 50 μm and 2 mm) and two leaf species with different qualities (i.e., Alangium chinense and Machilus leptophylla), with a total of 96 litter bags. Nitrogen (N) and phosphorus (P) uptake rates were measured in situ based on the spiraling model. We found that the decomposition rate of A.chinense was approximately seven times that of M. leptophylla in both streams. Moreover, in the urban stream, the litter decomposition rate (0.004 day−1) was one-third that of the forest stream (0.013 day−1), regardless of the litter species. Macroinvertebrates strongly contributed to litter decomposition in the forest stream, where decomposition rates were 1.8-fold higher in the coarse mesh compared to the fine mesh bags, while they had a negligible role in the urban stream (no significant difference between the two mesh bags). P uptake was higher (85-fold) and N uptake was lower (0.13-fold) in the urban compared to forest stream. Litter decomposition and nutrient uptake exhibit decoupled response. These findings show that litter decomposition by kcoarse/kfine metrics and the uptake of N and P are complementary and should be considered in the management and restoration of urban stream ecosystems.